Brief Client-Centered Motivational and Behavioral Intervention to Promote HPV Vaccination in a Hard-to-Reach Population: A Pilot Randomized Controlled Trial. (August 2016) - Joseph, Natalie Pierre; Bernstein, Judith; Pelton, Steve; Belizaire, Myrdell; Goff, Ginette; Horanieh, Nour; Freund, Karen M.
Objective . To evaluate the impact of a client-centered behavioral intervention (Brief Negotiated Interviewing) on mothers' human papillomavirus (HPV) vaccine knowledge and vaccination initiation for their adolescent daughters. Methods . We randomized mothers to intervention (n = 100) and control (n = 100) groups, and followed them over 12 months. Electronic medical records were reviewed to determine vaccination status. The primary outcome was receipt of the first vaccine. The secondary outcome was HPV vaccine knowledge among mothers. Results . Brief Negotiated Interviewing intervention mothers demonstrated increased knowledge about HPV (pre/post mean score of 5 to 10 out of a possible 11; P < .001) and significantly higher mean knowledge scores (10 vs 6, P < .001) than control mothers. However, initiation and completion rates of the vaccine were not significantly different between groups. Conclusions . Increasing HPV vaccine knowledge did not translate into increased vaccine uptake or completion of vaccination series. Future intervention must explore vaccine reminders to increase HPV vaccination rates.